Assessment of antiretroviral third agent virologic durability after initiation of first antiretroviral regimen. (June 2019) - Varriano, Brenda; Sandler, Ina; Loutfy, Mona; Steinberg, Samantha; Smith, Graham; Kovacs, Colin; Brunetta, Jason; Fletcher, David; Knox, David; Merkley, Barry; Chang, Benny; Tilley, David; et al.
Information on the virologic durability of modern antiretroviral regimens is important to clinicians. We aimed to describe virologic durability of first-line integrase strand transfer inhibitor (INSTI)-, nonnucleoside reverse transcriptase inhibitor (NNRTI)-, or protease inhibitor (PI)-based antiretroviral regimens. This was a retrospective study of antiretroviral-naïve patients that initiated first-line antiretroviral regimens with two nucleoside reverse transcriptase inhibitors and an INSTI, NNRTI, or PI between January 2006 and June 2016. The outcome was time to virologic failure, which was assessed by Kaplan–Meier survival analysis and Cox regression models. There were 780 patients (median age = 37 years [interquartile range (IQR) = 30–45], 93.3% male, 56.2% Caucasian, median HIV duration = 1.8 years [IQR = 0.4–5.4], baseline log10 viral load [VL]=4.6 [IQR = 4.1–5.1], and baseline CD4+ cell count = 320 cells/µl [IQR = 217–440]). In total, 189/780 were on a third agent INSTI, 339/780 on a third agent NNRTI, and 252/780 on a third agent PI. Kaplan–Meier survival probability revealed longer time to virologic failure for INSTI, followed by NNRTI then PI (p < 0.001). Multivariable Cox regression revealed that being on an INSTI regimen (aHR = 0.27; 95%CI = 0.18–0.41) or NNRTI regimen (aHR = 0.64; 95%CI = 0.47–0.87) versus PI regimen, frequent VL testing (per year), (aHR = 0.64; 95%CI = 0.47–0.87), and duration of ART (aHR = 0.22; 95%CI = 0.17–0.30) (years) were inversely associated with time to virologic failure, and log10 of baseline VL (aHR = 1.94; 95%CI = 1.58–2.39 per log10 ) increased risk. Virologic failure was delayed and virologic durability prolonged for INSTI- compared to NNRTI- and PI-based regimens, supporting current antiretroviral therapy guidelines.